Pemberdayaan Sekolah Dasar Sebagai Sekolah Siaga Sehat Melalui Intervensi Edukasi Kesehatan Preventif - Anggraini, Suci; Suyanto, Suyanto; Alfikri, Alif Kahfi; Indra, Dian Afifah; Ramadhan, Feldy Topani; Aini, Jum; Plantika, Lolita Dwi; Lubis, M. Daun Jihad Az-Zikri; Marcha, Niken Chairul; Mahrum, Rizkitaqiyah Aqela Eka; Khanzafira, Salsabila Aldea; Melinda, Siska; Lubis, Tri Wahyuni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Program Sekolah Siaga is a promotive and preventive intervention implemented at SDN 005 Bukit Timah, aimed at improving knowledge, fostering Clean and Healthy Living Behavior (CHLB), and strengthening the role of the School Health Unit (SHU). The program consisted of CHLB education, basic health screening (height, weight, oral and dental hygiene, and general health status), SHU cadre empowerment, and group tooth-brushing practice. Evaluation of 181 students showed improved understanding of CHLB, with an average correct response rate of 80.11%, alongside high enthusiasm during hygiene activities. Health screening identified cases of undernutrition, dental caries, and poor oral hygiene; among 65 respondents, 50% were categorized as severely malnourished. This program effectively enhanced teacher and student engagement and has potential as a sustainable model for school health promotion.